Strategi Penguatan Sosial Emosional Pada Siswa Sekolah Dasar - Dicky Rinaldi (Jurnal Pendidikan Tuntas, 2025)
The development of social and emotional skills in students has become a major focus in education, as the importance of non-academic aspects of life for long-term success increases. These skills include the ability to empathize, cope with stress, collaborate with others, and communicate effectively. Research shows that students who have social and emotional skills tend to be more successful in academic settings and in everyday life. In some schools, social and emotional skills programs have been integrated into the curriculum, with the goal of helping students develop self-confidence, emotional management skills, and healthy interpersonal relationships. These programs often include project-based activities, role-playing, group discussions, and mindfulness exercises. This article will explore the various approaches and strategies that educators can use to develop social and emotional skills in students. It will also discuss the challenges and opportunities in implementing these programs in schools, as well as strengthening the long-term benefits of student development. With a deeper understanding of educational psychology, it is hoped that educators can be more effective in supporting students’ holistic development, helping them achieve not only academic success but also emotional and social well-being.